Characterisation and inhibition studies of Helicoverpa armigera (Hübner) gut α‐amylase. Issue 9 (20th October 2014) - Kaur, Rimaljeet; Gupta, Anil K; Taggar, Gaurav K
Abstract BACKGROUND The survival of a devastating pest, Helicoverpa armigera, is mainly dependent on the availability of α‐amylase. Therefore, characterising H. armigera α‐amylase and targeting it with effective inhibitors could aid in reducing its damaging effects. RESULTS H. armigera gut possessed four isozymes of α‐amylase. The molecular weight of the major purified isozyme ranged from 79 to 81 kDa. The purified enzyme was identified to be α‐amylase on the basis of products formed from starch. The optimum pH and temperature were 10.0 and 50 °C respectively. The activation energy was 5.7 kcal mol−1. The enzyme showed high activity with starch and amylopectin, whereas dextrins were poor substrates. The Michaelis constant Km with starch, amylose and amylopectin was 0.45, 1.23 and 0.11 mg mL−1 respectively. ZnSO4, FeSO4, CuSO4, citric acid, oxalic acid and salicylic acid were potent inhibitors. ZnSO4, salicylic acid and pigeonpea α‐amylase inhibitor (∼21.0 kDa) acted primarily as competitive inhibitors, FeSO4 and citric acid displayed mainly anticompetitive behaviour, while CuSO4 and oxalic acid behaved mainly as non‐competitive inhibitors. CONCLUSIONS The identification of effective ecofriendly inhibitors could help in managing H. armigera infestation. © 2014 Society of Chemical Industry